CLUSTER APPROACHES OF COOPERATION OF PRESCHOOL EDUCATION ORGANIZATION WITH FAMILY, SCHOOL AND NEIGHBORHOOD (Web of Discoveries: Journal of Analysis and Inventions, 2024)
The article highlights the scientific and practical aspects of cluster approaches for the interaction of the organization of preschool education with the family, school and micro district. Ways of working with children and parents, neighbourhood, necessary recommendations for parents are given.